'Connoisseurs of Stone': Everyday Sarsen Stone in Neolithic Britain. (8th November 2022) - WHITAKER, KATY A.
Abstract : Sarsen stone boulders are familiar components of numerous British Neolithic megalithic monuments. Non-monumental uses of sarsen stone are, however, less well understood. This paper focuses on non-megalithic sarsen and its roles for communities, using case studies from three sites spanning the Neolithic in Wiltshire. Published data from Windmill Hill causewayed enclosure and analysis, using a new methodology, of recently excavated material from the West Kennet Avenue occupation site, and Marden henge enclosure are used to explore the varied ways in which sarsen was used. Rather than being an expedient 'mundane' stone this analysis demonstrates that non-megalithic sarsen could be just as meaning-laden as other more 'attractive' (larger, exotic) material. Daily encounters with sarsen stone for different purposes and in varied quotidian contexts afforded it with values which likely contributed to its use in monumental contexts. The importance of attending to sarsen in its multiple forms and contexts is thus made clear.